Extrinsic properties of unsaturated polyester resin-based hybrid composite reinforced with waste-fibers versus waste-fibers and talc: A comparative study - Nahar, Aynun; Dhar, Sajib Aninda; Pinky, Nigar Sultana; Ahmed, Aninda Nafis; Miah, Muhammed Yusuf; Alam, Md Ashraful; Robel, Fataha Nur; Bashar, Muhammad Shahriar; Mahmud, Monika; Gafur, Md Abdul (Bangladesh Journal of Scientific and Industrial Research, 2024)
This study demonstrates a comparative study on the mechanical, thermal, and morphological properties between waste-fibers/unsaturated polyester (WF/PE) and talc/waste-fibers/unsaturated polyester (T/WF/PE) hybrid composite. Here, reinforcing materials came from discarded coir doormats and jute sacks. The waste fibre was treated with NaOH and then embedded into the polyester matrix using a cold compression moulding technique. On the other hand, talc filler and waste-fibres reinforced polyester resin hybrid composite was developed using the same technique, and a comparative study was performed. WF/PE hybrid composite showed tensile and flexural strength of 36.67 MPa and 38.76 MPa respectively. Talc filler-filled T/WF/PE hybrid composite reported 23.95 MPa of tensile strength and 65.2 MPa of flexural strength. Average Leeb’s robust hardness (LRH) was found 495.667 and 524.75 for WF/PE and T/WF/PE respectively. T/WF/PE hybrid composite presented low-temperature thermal degradation compared to WNF/PE hybrid composite. Surface morphology studies showed that coagulation of fibres, voids, and fibre pullout at the inner interface of the composite was a common phenomenon for both composites. WF/PE composite showed higher electrical resistivity to applied voltage compared to T/WF/PE. Water absorption studies showed that talc filler boosted the water adsorption of the T/WF/PE hybrid composite. Bangladesh J. Sci. Ind. Res. 59(1), 17-26, 2024